The last patagonian cycad, austrozamia stockeyi gen. et sp. nov., early eocene of laguna del hunco, Chubut, Argentina - Wilf, Peter; Stevenson, Dennis Wm.; Cúneo, Néstor Rubén (Botany)
The cycads pose classic problems in evolutionary biogeography, owing to their far-flung extant distributions and the sparse fossil records of living genera. A noteworthy example is Tribe Encephalarteae of Family Zamiaceae, today consisting of Encephalartos (Africa) and the Australian genera Lepidozamia and Macrozamia. Numerous petrified trunks of Encephalarteae described from the Cretaceous of Patagonia, Antarctica, and India indicate far larger past distributions across Gondwana and subsequent extinctions. The only fossils close to the current range are Paleogene leaf fragments from Australia assigned to Lepidozamia and Macrozamia. Here, we report a large frond piece and several isolated leaflets of a compressed cycad, along with an associated spiny petiole, from the late-Gondwanan, 52.2 Ma Laguna del Hunco flora of Patagonia, Argentina. Austrozamia stockeyi gen. et sp. nov., has the novel combination of an Encephalartos-type leaf and Lepidozamia-type cuticle. The Australian Lepidozamia fossils, widely used for molecular clock calibrations, could also represent an extinct genus. Austrozamia stockeyi demonstrates survival of the Encephalarteae in Patagonia and presumably across Gondwana until its terminal phase, adding a striking new component to the growing list of South American plant extinctions associated with Antarctic separation and related climate changes. Fil: Wilf, Peter. State University of Pennsylvania; Estados Unidos Fil: Stevenson, Dennis Wm. New York Botanical Garden; Estados Unidos Fil: Cúneo, Néstor Rubén. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina